2001
DOI: 10.1088/0031-9155/46/8/309
|View full text |Cite
|
Sign up to set email alerts
|

A multiobjective gradient-based dose optimization algorithm for external beam conformal radiotherapy

Abstract: A multiobjective gradient-based algorithm has been developed for the purpose of dose distribution optimization in external beam conformal radiotherapy. This algorithm is based on the concept of gathering the values of all objectives into a single value. The weighting factors of the composite objective values are varied in different steps, allowing the reconstruction of the trade-off surfaces (three or more objectives) or curves (two objectives) which define the boundary between the feasible and non-feasible do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 19 publications
(19 reference statements)
0
69
0
1
Order By: Relevance
“…A recent focus of interest is multiobjective (MO) optimization, first introduced in (Cotrutz et al, 2001), which results in a representative set of Pareto-efficient solutions for various conflicting optimization objectives. Craft et al (Craft et al, 2005) showed how to find the Pareto-efficient space of solutions for MO optimization, and developed an interface for the planner to examine the way the tradeoffs change when the optimization parameters are altered.…”
Section: Tunable Parameters In Imrt Objective Functionsmentioning
confidence: 99%
“…A recent focus of interest is multiobjective (MO) optimization, first introduced in (Cotrutz et al, 2001), which results in a representative set of Pareto-efficient solutions for various conflicting optimization objectives. Craft et al (Craft et al, 2005) showed how to find the Pareto-efficient space of solutions for MO optimization, and developed an interface for the planner to examine the way the tradeoffs change when the optimization parameters are altered.…”
Section: Tunable Parameters In Imrt Objective Functionsmentioning
confidence: 99%
“…This means that IMRT and IMPT cannot be exploited to their full potential owing to limitations with inverse planning [58]. The concept of multi-objective Pareto optimisation (often known as MCO) has been introduced into radiotherapy treatment planning to overcome these problems [59]. A Pareto optimal treatment plan is not a single plan but a database of plans where each one represents a Pareto optimal solution which cannot be improved without worsening at least one other parameter [58].…”
Section: Optimisation Functions For Robust Proton Planningmentioning
confidence: 99%
“…is the structure-specific the importance factor. The values of the importance factors were determined empirically [27][28][29][30][31]. D?…”
Section: Bevd-guided Beam Orientation Optimizationmentioning
confidence: 99%
“…This Concept Award was awarded to the principal investigator (PI) for the period of July 1, 2001 June 30,2002. Because of the late arrival of the postdoctoral fellow (Dr. David Y. Yang) for this project, we have filed a no-cost extension to June 31, 2003 (see attached Assistance Agreement).…”
Section: Introductionmentioning
confidence: 99%